The Effectiveness of Performance Assessment in Project-Based Learning by Utilizing Local Potential to Increase the Science Literacy - Hairida Hairida; Tulus Junanto (International Journal of Pedagogy and Teacher Education, 2018)
Learning science requires students not only to remember the subject matter but also to develop science literacy. One of the ways to develop science literacy competencies is by applying performance assessment in project-based learning that utilizes local potential. This study aims to determine the effectiveness of performance assessment in local-potential-based learning on environmental pollution subject matter. The research was carried out using a quasi-experimental method with a pre- and post-test design. The sample for the research is 7th grade students in Pontianak, and the data collection tool is an observation sheet using a science literacy rubric test. The research results show that performance assessment of project-based learning utilizing local potential can increase students’ science literacy.